Upaya Pencegahan dan Penanggulangan Tindak Pidana Terorisme oleh Detasemen Khusus 88 Anti Teror - Muslim, M Imam; Ahmad, Ruben; Martini, Martini (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
Terrorism is categorized as an extraordinary crime that threatens national security, state stability, and public safety. Its countermeasures require specific legal instruments and specialized law enforcement agencies with strategic authority, one of which is the Special Detachment 88 Anti-Terror (Densus 88 AT) of the Indonesian National Police. This study aims to analyze the preventive and repressive efforts undertaken by Densus 88 AT in combating terrorism, particularly in the case of the Jama’ah Islamiyah (JI) network in South Sumatra, and to identify the obstacles encountered in its implementation. This research employs a normative-empirical legal research method with statutory, conceptual, and case approaches. The data were obtained through library research examining statutory regulations, legal doctrines, and relevant literature, as well as field research conducted through interviews with Densus 88 AT officers, community leaders, legal academics, and former terrorism convicts. The findings indicate that the preventive measures carried out by Densus 88 AT in South Sumatra include counter-radicalization, counter-ideology, and counter-narrative strategies implemented through socialization programs in schools, government institutions, private sectors, mass media, as well as guidance and empowerment programs for former terrorism convicts. Meanwhile, repressive measures are conducted through investigation, arrest, search and seizure, and law enforcement proceedings against members and supporters of the Jama’ah Islamiyah network, including those involved in terrorism financing. The obstacles faced include the widespread dissemination of radical ideology through digital media, the clandestine and organized nature of terrorist networks, limited community participation, and the challenge of maintaining a balance between effective law enforcement and the protection of human rights. Based on these findings, it can be concluded that the counterterrorism efforts undertaken by Densus 88 AT in South Sumatra have been implemented through a comprehensive approach integrating preventive and repressive measures. The effectiveness of this strategy depends on cross-sectoral synergy, strengthening societal ideological resilience, and the professionalism of law enforcement officers in carrying out their duties in accordance with the principles of the rule of law.